Pedagogical And Psychological Factors Of Organizing Vocational Education And Education On The Basis Of Youth Psychological Characteristics In Continuous Education - Rafik Gayratovich Rahmatov (Euro Asian Journal Publishing, 2024)
In this article, socio-pedagogical-psychological factors related to young people's choice of profession are theoretically analyzed, paying attention to young psychological characteristics, carrying out education of the child's interests and abilities on the basis of continuity in the family, MTT and school, youth in adolescence It is analyzed to coordinate and support the trajectory of a stable professional and educational direction with educational content.
Keywords: Education; career trajectory; architecture of social activity